Independent Power Producer (IPP) Participation: Solution to Nigeria Power Generation Problem - Agboola, O. Phillips (Int Assoc Engineers-Iaeng, 2011)
Nigeria is locked up in an energy poverty cycle since the 80's when the nation neglected signals to improve upon its power generation capacity. The poverty of energy in Africa is raising concern despite her huge resources ranging from Oil/Gas to renewable resources. This work evaluates the independent power producer participation in the Nigeria power sector and the role the government need to play to attract investment. Capacity building measures were suggested to help facilitate the involvement of the IPP firms to end the power crises in the country. This work also reviews the Nigeria power sector and the challenges it faces over a long period of time. This work will serve as a guideline to government and politician charged with responsibility to reform the power sector in Nigeria.
World Congress on Engineering (WCE 2011) -- JUL 06-08, 2011 -- Imperial Coll, London, UNITED KINGDOM
Keywords: IPP; power generation; energy poverty; Nigeria; electricity; power reform